2002
DOI: 10.4049/jimmunol.169.1.375
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN as a Natural Adjuvant for a Protective Immune Response: Lessons from the Influenza Vaccine Model

Abstract: The identification of natural adjuvants capable of selectively promoting an efficient immune response against infectious agents would represent an important advance in immunology, with direct implications for vaccine development, whose progress is generally hampered by the difficulties in defining powerful synthetic adjuvants suitable for clinical use. Here, we demonstrate that endogenous type I IFN is necessary for the Th1 type of immune response induced by typical adjuvants in mice and that IFN itself is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
150
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(159 citation statements)
references
References 43 publications
8
150
1
Order By: Relevance
“…Most interestingly, IL-15 is produced by dendritic cells upon stimulation with IFN type I. 41 This cytokine is not only frequently used in the treatment of metastatic melanoma but it has also been shown to provide adjuvancy in the induction of humoral and CTL responses [42][43][44] and to promote in experimental models of infection or cancer, the expansion of CD8þ T cells with a memory phenotype. 45 These immunoregulatory effects might be, at least in part, attributed the induction of paracrine IL-15 production.…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, IL-15 is produced by dendritic cells upon stimulation with IFN type I. 41 This cytokine is not only frequently used in the treatment of metastatic melanoma but it has also been shown to provide adjuvancy in the induction of humoral and CTL responses [42][43][44] and to promote in experimental models of infection or cancer, the expansion of CD8þ T cells with a memory phenotype. 45 These immunoregulatory effects might be, at least in part, attributed the induction of paracrine IL-15 production.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the best strategy to boost subunit flu vaccine formulation is to restore IFN type I-associated activities that are lost during the purification process. Accordingly, coadministration of type I rIFN with a subunit influenza vaccine in mice was shown to increase protection against virus challenge (7). Alternatively, subunit flu vaccine formulation immunogenicity could be restored by incorporation of IFN inducers such as the TLR9 agonist (5).…”
mentioning
confidence: 99%
“…Recently, studies have focused on the use of cytokines as intranasal vaccine adjuvants to enhance the immunogenicity of the DNA vaccine because of their potent effects on innate and adaptive immunity as well as functional diversity of immune responses. Studies have shown that cytokines, such as IL-12 [13,14] , IL-2 [15] , IL-15 [16] , type I interferon (IFN) [17,18] , IL-1 [19] , IL-6 [20] , and granulocyte-macrophage colony-stimulating factor (GM-CSF) [21] , enhanced antigen-specific immunity following delivery with different antigens.…”
Section: Introductionmentioning
confidence: 99%